The Analysis of Taboo Language as a Form of Racial Discrimination on Blackkklansman Film by Spike Lee - Pradnyana, Komang Geni (International Journal of Language and Literature, 2022)
This study aimed at identifying the types and meaning of taboo languages which were considered as racial discrimination on the film entitled BlacKkKlansman. This study used textual analysis to analyze the subject as a text where it could be understood and got the meaning. The source of data of this study was film entitled BlacKkKlansman. Batistella stated that there were four types of taboo language namely; epithet, profanity, vulgarity and obscenity. To get the meaning the taboo language the data was analyzed using denotation and connotation by Barthes. Denotation used to get the literal meaning and connotation for secondary meaning. This study found 4 types of the taboo language with 52 total data. The data were consisted of 20 epithet data, 11 profanity data, 10 vulgarity data and 11 obscenity data. In conclusion, the meaning of the taboo language was a form of racial discrimination towards certain group of race.